Composites of Single/Double Perovskites as Cathodes for Solid Oxide Fuel Cells. Issue 7 (15th April 2016) - Bu, Yunfei; Chen, Yu; Wei, Tao; Lai, Samson; Ding, Dong; Sun, Haibin; Zhen, Dongxin; Xiong, Xunhui; Zhong, Qin
Abstract: The state‐of‐art cathode materials PrBaCo2 O5+ δ (PBC) and La0.4 Sr0.6 Co0.2 Fe0.8 O3− δ (LSCF) are mixed into a composite cathode for intermediate‐temperature solid oxide fuel cells (IT‐SOFCs). Analysis by X‐ray powder diffraction (XRD) and scanning electron microscopy (SEM) demonstrates that a structure comprising a single and double perovskite is obtained upon sintering in air at 1000 °C. Possible chemical interdiffusion between PBC and LSCF grains is further investigated by transmission electron microscopy and scanning transmission electron microscopy combined with electron energy loss spectroscopy. The composite cathode PBC+LSCF (with mass ratio 6:4) shows improved performance compared to either PBC or LSCF alone, achieving total area resistance (ASR) values in air of 0.017, 0.032, 0.07, 0.16, and 0.32 Ω cm −2 at 800, 750, 700, 650, and 600 °C, respectively. The PBC‐LSCF 64 cell delivered power densities of 1103 mW cm −2 at 750 °C, which were enhanced by 26 % and 35 % compared to the initial PBC and LSCF powders, respectively. Abstract : And variations perov : Solid oxide fuel cells (SOFCs) are clean, efficient energy converters with excellent fuel flexibility. Reducing the working range of SOFCs towards intermediate temperatures is recognized as an essential step towards commercialization. Composite cathodes comprising state‐of‐the‐art single and double perovskites are prepared and used as cathodes. The materials enable better performance at lower operating temperatures.